The Effect of Multisensory Teaching Method on The Students’ Reading Achievement - Diani Syahputri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study  aims    to investigate  the  effect  of  Multisensory Teaching Method ontheStudents’ Reading Achievement.Thisresearchappliedexperimentalresearch.The populationof thisresearchwastakenfromtheSevengradeandthesecondyearstudentsof juniorhigh school in SMPSwasta PGRI 3 Medanatacademic 2017/2018. There were 3 classes consisting 113 students. This research  was  applied cluster random sampling.  This  research  used  experimental researchdesignnamely Onegrouppre-testandpost-test,Therefore,theresearch tookoneclassastheexperimentalclass.  The samplewastakenfromthe students in VII-1 who consisted of 38 students. Theresearcher were given treatment  by  Multisensory Teaching Method.  The  instrument  of research is  amultiplechoice test  whichconsistof20items.Thedatawere analyzed by using t-test formula. The result of the data showed that tobserve 13.3 > ttable 1.68 with degree of freedom (df)= n-k. The hypothesis was accepted. It proves that Multisensory Teaching Method significantly effect to the students’ reading achievement.